Skala TAI-G Untuk Kecemasan Menghadapi Ujian Pada Siswa Sekolah Menengah Atas - Nayu, Hasnaa' Zahuna (Faculty of Teacher Training and Education, Universitas Muhammadiyah Surakarta, 2020)
Anxiety facing exams refers to the student's tendency to understand evaluativ situations where their performance will be assessed, such as high-risk exams, as they are very threatening. The threat here is their self-esteem, fear will be judged negatively by teachers, friends, or parents. The purpose of this research is to seek the validity and reliability of the TAI-G scale. This research uses a quantitative approach. The number of samples of this study was 101 SMA/SMK students in Magelang with an age range of 15-17 years. Sampling in this study used simple random sampling techniques. The results of the analysis show 21 items declared valid with a correlation of item-Total 0.25, 1 invalid item with a total-item correlation of 0.25, and an alpha reliability of 0.907.